Modeling evaluation of a direct-expansion solar-assisted heat pump water heater using R410A. (April 2017) - Kong, X.Q.; Li, Y.; Lin, L.; Yang, Y.G.
Highlights: A direct-expansion solar-assisted heat pump system by using R410A as refrigerant is designed. A numerical model is developed to estimate the thermal performance of the system. The effects of the refrigerant charge quantity on the performance parameters of the system are analyzed. The effects of various parameters have been simulated and analyzed on the thermal performance of the system. Abstract: A direct-expansion solar-assisted heat pump (DX-SAHP) system by using R410A as refrigerant is described, which can supply domestic hot water during the whole year. Based on the distributed parameter and homogeneous flow models of collector/evaporator and condenser, the lumped parameter models of compressor and electronic expansion valve, and the refrigerant charge model, a numerical model is developed to estimate the thermal performance of the system. Given the structure parameters, meteorological parameters, initial and final water temperatures, for a fixed superheat degree, the effects of the refrigerant charge quantity on the performance parameters of the system are analyzed, such as compressor power, heat gain of collector, heating time, collector efficiency and system COP. Furthermore, for a fixed refrigerant charge quantity, the effects of various parameters, including solar radiation, ambient temperature, compressor speed and initial water temperature, have been simulated and analyzed on the thermal performance of the system.